2019
DOI: 10.3390/v11111013
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Temperature in Transmission of Zoonotic Arboviruses

Abstract: We reviewed the literature on the role of temperature in transmission of zoonotic arboviruses. Vector competence is affected by both direct and indirect effects of temperature, and generally increases with increasing temperature, but results may vary by vector species, population, and viral strain. Temperature additionally has a significant influence on life history traits of vectors at both immature and adult life stages, and for important behaviors such as blood-feeding and mating. Similar to vector competen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 266 publications
(380 reference statements)
1
71
0
4
Order By: Relevance
“…Firstly, the rearing temperature, which is an extrinsic factor that affects direct and indirectly the Ae. albopictus susceptibility to arbovirus [23,40,41]. The environmental factors in which mosquitoes were reared, may have played a crucial role for ZIKV transmission of Spanish Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the rearing temperature, which is an extrinsic factor that affects direct and indirectly the Ae. albopictus susceptibility to arbovirus [23,40,41]. The environmental factors in which mosquitoes were reared, may have played a crucial role for ZIKV transmission of Spanish Ae.…”
Section: Discussionmentioning
confidence: 99%
“…The storage conditions may not be optimal, and hence some mosquitoes may therefore perish before they are collected. Furthermore, DENV infectivity is temperature-related: higher temperatures hasten the spread of DENV within the mosquito [ 32 ]. Two studies have reported the successful detection of DENV within infected mosquitoes using NS1 Ag or qPCR after multiple freeze–thaw cycles and/or drying [ 9 , 13 ], even for mosquitoes that had been desiccated for 30 days.…”
Section: Discussionmentioning
confidence: 99%
“…A key principle of thermal biology is that the effects of temperature on mosquito-borne disease transmission are unimodal with lower and upper limits. Starting at zero for a lower temperature limit, their value increase with the temperature until a maximum, then it starts to decrease until an upper temperature limit is reached [23]. Such behavior can be well approximated by a Gaussian distribution.…”
Section: A Influence Of Environmental Factors On Vector-borne Diseasesmentioning
confidence: 94%